1992
DOI: 10.1099/00221287-138-12-2715
|View full text |Cite
|
Sign up to set email alerts
|

Purification and amino acid sequence of sakacin A, a bacteriocin from Lactobacillus sake Lb706

Abstract: Sakacin A, a bacteriocin produced by Lactobacillus sake Lb706 and which inhibits the growth of Listeria monocytogenes, was purified to homogeneity by ammonium sulphate precipitation and ion-exchange, hydrophobicinteraction and reversed-phase chromatography. The complete amino acid sequence of sakacin A was determined by Edman degradation. The bacteriocin consisted of 41 amino acid residues and had a calculated Mc of 4308.7, which is in good agreement with the value determined by mass spectrometry. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
136
0
6

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 25 publications
5
136
0
6
Order By: Relevance
“…This result is in accord with the previous observation that the isolated immunity protein does not bind significantly to the parent bacteriocin CbnB2 in vitro (13). Genes for related immunity proteins have been found in other LAB bacteriocin-producing systems (17,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 82%
“…This result is in accord with the previous observation that the isolated immunity protein does not bind significantly to the parent bacteriocin CbnB2 in vitro (13). Genes for related immunity proteins have been found in other LAB bacteriocin-producing systems (17,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 82%
“…The group contains at least 17 bacteriocins, of which pediocin PA-1 (Biswas et al, 1991 ;Henderson et al, 1992 ; Marugg et al, 1992 ;Nieto Lozano et al, 1992), leucocin A UAL-187 (Hastings et al, 1991), mesentericin Y105 (He! chard et al, 1992), sakacin P (Tichaczek et al, 1992) and curvacin A (identical to sakacin A ; Tichaczek et al, 1992 ;Holck et al, 1992) were the first to be identified. All pediocin-like bacteriocins are cationic, contain between 35 and 50 amino acid residues, permeabilize target-cell membranes, and have very similar primary structures, but they differ markedly with respect to their target-cell specificities (Chen et al, 1997a, b ; Chikindas et al, 1993 ;Eijsink et al, 1998 ; Fimland et al, 1996 Fimland et al, , 1998Fimland et al, , 2000Johnsen et al, 2000 ;Nes et al, 2002).…”
mentioning
confidence: 99%
“…The family contains at least 15 different bacteriocins, of which pediocin PA-1 (3,19,23,30), leucocin A UAL-187 (17), mesentericin Y105 (18), sakacin P (35) and curvacin A (identical to sakacin A [20,35]) were the first to be identified. All pediocin-like bacteriocins are cationic, contain between 35 and 50 amino acid residues, permeabilize target cell membranes, and have very similar primary structures but differ markedly with respect to their target cell specificity (5-7, 10-14, 22, 24, 29, 32, 37).…”
mentioning
confidence: 99%